DEVELOPMENT OF MOBILE LEARNING BASED ON A SCIENTIFIC APPROACH TO LEARNING ELEMENTARY SCHOOL THEMES - Suhardi; Indri Astuti; Dede Suratman (Jurnal Scientia, 2022)
This study aims to develop a scientific-based mobile learning application for thematic learning that is suitable for use in elementary school learning. The research method used is Research and Development with the development model using ADDIE which has five stages, namely analysis, design, development, implementation, and evaluation. The instrument used in the study used an assessment sheet from material experts, media experts, teacher assessments, and student trials. This research was tested on 42 elementary school students. The results showed that from the validation of the material experts a percentage of 90.25% was obtained, then the results of the validation by media experts with a percentage of 91.00%, and the results of the assessment by the teacher obtained a percentage of 87.50% in the appropriate category. The test was carried out on students, the percentage of learning media quality was 91.50% with a very decent category. Based on the results of data acquisition, it shows that the scientific-based mobile learning application in thematic learning is feasible to be used as a learning medium for fourth grade elementary school students. Keywords: Mobile Learning, Scientific, Thematic, ADDIE Model.